Effects of environment factors on the carbon fluxes of semi-fixed sandy land recovering from degradation - Niu, Yayi; Li, Yuqiang; Liu, Wei; Wang, Xuyang; Chen, Yun (Frontiers in Ecology and Evolution, 2023)
Shrub-dominated ecosystems in the semiarid Horqin Sandy Land are important terrestrial ecosystems, and substantially affect global ecological health and security. However, there have been few studies of climate change’s effects on the carbon fluxes (NEE, net ecosystem exchange; Reco, ecosystem respiration; GPP, gross primary productivity) when these ecosystems are recovering from degradation. We used the eddy covariance technique to determine carbon fluxes and climatic conditions in this ecosystem from 2017 to 2021. The semi-fixed sandy land functioned as a carbon sink in wet years (NEE equaled –14.14 and –126.14 g C m-2 yr-1 in 2019 and 2021, respectively), but was a carbon source in dry years (NEE equaled 48.50 and 51.17 g C m-2 yr-1 in 2017 and 2020, respectively) and a normal year (NEE equaled 74.66 g C m-2 yr-1 in 2018). As expected in these usually water-limited ecosystems, water availability (precipitation and soil water content) were the dominant drivers of NEE, Reco, and GPP, but temperature and photosynthetic photon flux density (PPFD) also played important roles in regulating NEE, Reco and GPP in this recovering semi-fixed sandy ecosystem. With future precipitation and temperature increases, and continuing vegetation restoration, carbon sequestration by this ecosystem is expected to increase. Long-term observations will be necessary to reveal the true source and sink intensities and their response to environmental factors.